Impact of merger & acquisition announcements on share price – a case of selected indian listed companies - V, Poornima; V, Chitra (Journal of Management and Science, 2013)
This study examines the impact of merger and acquisition announcements on share price towards acquiring companies during the year 2012 listed on National Stock Exchange, India. The investigation has been carried out using traditional event study methodology. The present study is an empirical analysis to examine the stock price reaction to information content of merger and acquisition announcements with a view of finding whether Indian stock market is semi-strong efficient or not. Impact has been analyzed between 7 days from the date of merger and acquisition announcement. The result divulges that around the announcement period the returns for the acquiring companies are higher. In the post merger announcement period there is an upward trend in the cumulative returns implying a positive result of the merger.